THE RATE OF 45Ca UPTAKE BY TWO CORALS SPECIES AT WATERS OF PULAU BURUNG, BANGKA-BELITUNG PROVINCE - Dahlan, Zulkifli; Diansyah, Gusti; Ulqodry, T. Zia; Citraresmin , Ania (Jurnal Ilmiah Aplikasi Isotop dan Radiasi, 2013)
Coral reefs transplantation is the most technique used for coral reefs rehabilitation, at the present. Recently the 45Ca technique has been using for determining growth appearances in corals because of its ability to calculate the calcification process. For this reason, the study on the rate of 45Ca uptake by natural corals Acropora formosa and Acropora nobilis was carried out between June and December 2009 at the waters of Pulau Burung Island, Bangka-Belitung Province. The coral fragments of about 5 cm were harvested and put into a PVC container filled with 2 liters of fresh sea water, then incubated with 45CaCl2 solutions with an activity of 11.04 μCi/ml for 8 hour under fluorescent light. After the incubation, the “labeled” coral fragments were transplanted to where they have been taken from, and after such period will be re-harvested to determine their 45Ca uptake content. The results showed that the 45Ca technique was a reliable method to calculate the rate 45Ca uptake by coral fragments, which were studied in different depths and time periods of light exposure. There was a significant difference in the 45Ca uptake by the two different coral species. A. formosa up took more 45Ca than A. nobilis did. The highest 45Ca uptake was shown by A. formosa at 5 m. This was true for all the lengths of time to light exposure (1, 3, 5 and 7 hours). Different pattern of 45Ca uptake showed by A. nobilis at 10 m depth, where it could be recognized that after a drop of 45Ca the uptake increase continuously until the end of the light exposure (7 hours). The difference in 45Ca uptake between the coral fragments is assumed to be influence by light and the algae species living symbiotically with the coral species that will further influence the CO2-fixation. This process will influence the calcification process, which is expressed in 45Ca uptake. Further studies should be carried out to exactly gathered data of all the factors which could influence the calcification process by coral reefs, the factors could be CO2-fixation, flow of sedimentation, etc.